2001
DOI: 10.1111/j.1553-2712.2001.tb00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Mandibular Trauma: ROC Analysis

Abstract: Abstract. Objectives:To compare the diagnostic efficacies of panoramic radiographs, mandibular trauma series, and digitized radiographs for detection of fractures of the mandible. Methods: Fractures were induced using blunt trauma in 25 cadaver mandibles. Panoramic radiographs, digitized radiographs, and mandibular series comprising an anteroposterior view, two lateral oblique, and a reverse Towne's were used. Six observers recorded their diagnoses using a five-point confidence rating scale. The data were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Panoramic radiography can provide useful diagnostic information in cases of mandibular including condylar fractures (16, 34, 49). But panoramic radiographs have shortcomings in detecting the most common fracture of the mandible in the condyle area (49).…”
Section: Discussionmentioning
confidence: 99%
“…Panoramic radiography can provide useful diagnostic information in cases of mandibular including condylar fractures (16, 34, 49). But panoramic radiographs have shortcomings in detecting the most common fracture of the mandible in the condyle area (49).…”
Section: Discussionmentioning
confidence: 99%
“…Panoramic radiography is superior to other conventional radiography and it is adequate in evaluating mandibular fractures 8,9,16. With the growing use of the panoramic radiography, the occasions for general dentists to diagnose mandibular fractures have been increasing.…”
Section: Discussionmentioning
confidence: 99%
“…It means that they had a considerable knowledge on the fracture interpretation. The mandibular condyle is considered as one of the most difficult regions to detect fractures,5,9,17,18 and this is especially true for the sagittal splitting fracture of the condylar head. This study showed that the sensitivity of the condylar fractures was different according to the location of the fractures.…”
Section: Discussionmentioning
confidence: 99%
“…1 These plain radiographs are technique sensitive, time consuming, difficult to interpret and expose patients to high levels of radiation. 2 In comparison to the MS, OPG radiographs are superior in identifying mandibular fractures. 2,3 The MS offers one advantage over the OPG: they are more suitable for uncooperative patients and patients who unable to stand upright and motionless for short periods.…”
Section: Plain Film Radiographsmentioning
confidence: 99%
“…Healing follows spontaneous exfoliation of the fragment or surgical removal. 2 I would like to share this reference with your readers as I hope they will find it interesting; in five years of dental school this condition was never mentioned. …”
mentioning
confidence: 99%